2014
DOI: 10.1111/crj.12210
|View full text |Cite
|
Sign up to set email alerts
|

Exercise‐induced respiratory symptoms and allergy in elite athletes: Allergy and Asthma in Polish Olympic Athletes (A2POLO) project within GA2LEN initiative

Abstract: High prevalence of exercise-induced respiratory symptoms among top athletes is not reflected by asthma diagnosis. As it was expected, our data confirm that - in diagnosis of EIA - lung function testing alone is not useful, whereas reversibility tests are of limited value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 23 publications
2
22
0
2
Order By: Relevance
“…Katelaris et al used comparable methodology to our study, asking Australian Olympic athletes to self-report of symptoms and found rhinitis in 56 % [16]. By comparison, studies which rely upon previous physician diagnosis tend to report much lower prevalence than our population: 25 % of German Olympic athletes [25] had a previous diagnosis of allergic rhinitis; 26.2 % of in Italian Olympic athletes [7]; and 27 % in Polish Olympians [17]. Reliance upon previous physician diagnosis has some obvious limitations, requiring the athlete to have attended for these symptoms and a doctor to have made the diagnosis and expressly communicated it.…”
Section: Discussionsupporting
confidence: 46%
“…Katelaris et al used comparable methodology to our study, asking Australian Olympic athletes to self-report of symptoms and found rhinitis in 56 % [16]. By comparison, studies which rely upon previous physician diagnosis tend to report much lower prevalence than our population: 25 % of German Olympic athletes [25] had a previous diagnosis of allergic rhinitis; 26.2 % of in Italian Olympic athletes [7]; and 27 % in Polish Olympians [17]. Reliance upon previous physician diagnosis has some obvious limitations, requiring the athlete to have attended for these symptoms and a doctor to have made the diagnosis and expressly communicated it.…”
Section: Discussionsupporting
confidence: 46%
“…On the other hand, our study showed an approximate fourfold increased risk for elevated FE NO -values for asthmatic athletes. This might suggest an insufficient control of the asthma status and might explain asthma symptoms during exercise despite normal lung function test results at rest [74]. Unfortunately, we did not implement an asthma control questionnaire [75].…”
Section: Clinical Measurementsmentioning
confidence: 98%
“…Studies of the presence of periostin in bronchial lavages, sputum and exhaled breath condensate (EBC) have been carried out but these findings remain scarce and inconclusive. Exercise‐induced asthma and bronchoconstriction are believed to be underestimated in professional athletes . Changes in the serum levels of innate immunity proteins are known to occur in professional athletes during the training season, in response to exercise load and ambient training conditions .…”
Section: Introductionmentioning
confidence: 99%
“…Exercise-induced asthma and bronchoconstriction are believed to be underestimated in professional athletes. 8,9 Changes in the serum levels of innate immunity proteins are known to occur in professional athletes during the training season, in response to exercise load and ambient training conditions. 10 Increases in serum periostin may be associated with exercise-induced bronchoconstriction but little evidence is available to support this.…”
mentioning
confidence: 99%